Azithromycin for prevention of exacerbations in severe asthma (AZISAST): a multicentre randomised double-blind placebo-controlled trial. Issue 4 (3rd January 2013) - Brusselle, Guy G; VanderStichele, Christine; Jordens, Paul; Deman, René; Slabbynck, Hans; Ringoet, Veerle; Verleden, Geert; Demedts, Ingel K; Verhamme, Katia; Delporte, Anja; Demeyere, Bénédicte; Claeys, Geert; et al.
Abstract : Background: Patients with severe asthma are at increased risk of exacerbations and lower respiratory tract infections (LRTI). Severe asthma is heterogeneous, encompassing eosinophilic and non-eosinophilic (mainly neutrophilic) phenotypes. Patients with neutropilic airway diseases may benefit from macrolides. Methods: We performed a randomised double-blind placebo-controlled trial in subjects with exacerbation-prone severe asthma. Subjects received low-dose azithromycin (n=55) or placebo (n=54) as add-on treatment to combination therapy of inhaled corticosteroids and long-acting β2 agonists for 6 months. The primary outcome was the rate of severe exacerbations and LRTI requiring treatment with antibiotics during the 26-week treatment phase. Secondary efficacy outcomes included lung function and scores on the Asthma Control Questionnaire (ACQ) and Asthma Quality of Life Questionnaire (AQLQ). Results: The rate of primary endpoints (PEPs) during 6 months was not significantly different between the two treatment groups: 0.75 PEPs (95% CI 0.55 to 1.01) per subject in the azithromycin group versus 0.81 PEPs (95% CI 0.61 to 1.09) in the placebo group (p=0.682). In a predefined subgroup analysis according to the inflammatory phenotype, azithromycin was associated with a significantly lower PEP rate than placebo in subjects with non-eosinophilic severe asthma (blood eosinophilia ≤200/µl): 0.44 PEPs (95% CI 0.25 to 0.78) versus 1.03 PEPs (95% CI 0.72 to 1.48) (p=0.013). Azithromycin significantly improved the AQLQ score but there were no significant between-group differences in the ACQ score or lung function. Azithromycin was well tolerated, but was associated with increased oropharyngeal carriage of macrolide-resistant streptococci. Conclusions: Azithromycin did not reduce the rate of severe exacerbations and LRTI in patients with severe asthma. However, the significant reduction in the PEP rate in azithromycin-treated patients with non-eosinophilic severe asthma warrants further study. ClinicalTrials.gov number: NCT00760838.